PENDAYAGUNAAN KELOMPOK DISKUSI MAHASISWA DALAM MENANGKAL PAHAM RADIKALISME DAN PAHAM TERORISME DI LINGKUNGAN PERGURUAN TINGGI - Humaizi; R. Hamdani Harahap; Ridwan Hanafiah; Rudi Salam Sinaga (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Terrorism groups have obviously put their attention to recruiting new members of educated people like college-age students, a number of terrorists who have been caught showing their status as students or college students. We consider one of the most important ways to be cultivated in a college environment by conducting radical anti-radical and anti-terrorist campaigns and campaigning the right way to deal with situations that focus on radical thinking and action and terrorism. This study will look at students' perceptions within the Faculty of Social and Political Sciences of the University of North Sumatra against the danger of radical understanding and understanding of terrorism and prevention solutions for the safety of their surrounding environment. The method used in this study is literature study, documentation and focus group discussion (FGD). The results of this study show a strong appreciation of student discussion groups on the intent and purpose of this activity